Gambaran Perkembangan Moral dan Spiritual Siswa di MTs Cerdas Murni - Amanda Zulfani Harahap; Ade Chita Putri Harahap; Maulida Amelia Putri; Hasanah Hasibuan; Suryani Suryani; Pratama Hajariansyah (Tarbiatuna: Journal of Islamic Education Studies, 2023)
AAmanda Zulfani Harahap3, Recky Pratama Hajariansyah6 1,2,3,4,5,6 Universitas Islam Negeri Sumatera Utara Medan , 2, amandazulfaniharahap@gamil.com3, Suryani Ulfa5,, suryani02102@gmail.com5, Reckypratama3@gmail.com6 ABSTRACK. The moral and spiritual development of students at Mts Intelligent Pure is the moral development that is still low and not good which leads to negative things because there is juvenile delinquency such as dating cases. This is where the school's kids have struggled to keep the lines of demarcation between boys and girls.This can happen because of problematic families with sub-indicators of lack of attention, lack of affection, broken homes, authoritarian parents and over-affectionate parents as well as technological advancements such as the internet where children and adolescents easily access pornography, the curiosity of teenagers. The goal of this study was to learn more about the moral and spiritual growth of MTs Intelligent Pure pupils. Inductive reasoning techniques are applied in this study's qualitative research methodology. The purpose of this study is to identify the contributing causes to juvenile delinquency at MTS Smart Pure, Tembung. The results of the research conducted are to develop the moral and spiritual development of students at MTs Smart Pure in a better and positive direction and to open students' minds so they can think more broadly. Keywords: Development, Moral, Spiritual